Unauthorized Creation and Modification of Real Estate in Russian Federation - Yushchenko, Natalya Anatolyevna (2021)
The scientific article is aimed at a comprehensive study of unauthorized actions in relation to real estate in Russia. It is established that today there is no comprehensive concept of unauthorized actions in the legal literature and Russian legislation.